UKURAN PERUSAHAAN MEMODERASI PENGARUH PROFITABILITAS, CURRENT RATIO, DAN TINGKAT PAJAK TERHADAP DEBT EQUITY RATIO - Purwansyah, Fetiah Dwi; Yuliana, Indah (JURNAL EKBIS, 2023)
This study aims to determine the effect of profitability, tax rate, and current ratio on the debt equity ratio , namely the ratio in the calculation of capital structure. By including company size as a moderating variable, it is hoped that it can strengthen or weaken the relationship between variables in companies engaged in the financial sector and the trade, services and investment sectors in the period 2018 to 2020. The test is carried      out      using      statistical      software Smart PLSThe results showed that the profitability and current ratio partially had a significant negative effect on the debt equity ratio, while the tax rate partially had no effect on the debt equity ratio. Meanwhile, simultaneously profitability, CR, and tax rate have a significant negative effect. Meanwhile, the size of the company partially can only moderate the relationship between profitability and current ratio to debt equity ratio, and current ratio partially had a significant negative effect on the debt equity ratio, while the tax rate partially had no effect on the debt equity ratio. Meanwhile, simultaneously profitability, CR, and tax rate have a significant negative effect. Meanwhile, the size of the company partially can only moderate the relationship between profitability and current ratio to debt equity ratio